Cultivating Health Cultivating Health: Traditional Alcoholic Drink 'Tuak' as a Potential Functional Drink for Regulating Blood Glucose Levels while Keeping Cultural Significance Intact: Traditional Alcoholic Drink 'Tuak' as a Potential Functional Drink for Regulating Blood Glucose Levels while Keeping Cultural Significance Intact - wella apriwidyanti; Annisya Dwi Putri Zulmi; Diana Zahra Safitri; Khairahma Khairahma; Ramlan Silaban (DIVERSITAS HAYATI, 2024)
This research examines the potential for developing traditional alcoholic drinks using Raru (Cotylelobium melanoxylon Pierre) as an additional ingredient in the fermentation of tuak. Tuak, as a traditional alcoholic drink that is popular in many regions in Indonesia, plays an important cultural role in traditional celebrations. The advantages of palm wine as a traditional alcoholic drink include its natural sweet taste, good nutritional content, low alcohol content and affordable price. By analyzing the potential of Raru as an additional ingredient in making palm wine, this research seeks to develop traditional alcoholic drinks that not only maintain cultural and traditional aspects, but also provide additional health benefits, especially in lowering blood sugar levels, by launching a new product called ' 'RaruReserve: Healthy Tuak”